Transcriptional changes in the brains of cattle orally infected with the bovine spongiform encephalopathy agent precede detection of infectivity - Tang, Yue; Xiang, Wei; Hawkins, Steve A. C.; Kretzschmar, Hans A.; Windl, Otto (Journal of Virology, 2009)
Bovine spongiform encephalopathy (BSE) is a fatal, transmissible, neurodegenerative disease of cattle. BSE can be transmitted experimentally between cattle through the oral route, and in this study, brain tissue samples from animals at different time points postinoculation were analyzed for changes in gene expression. The aims of this study were to identify differentially regulated genes during the progression of BSE using microarray-based gene expression profiling and to understand the effect of prion pathogenesis on gene expression. A total of 114 genes were found to be differentially regulated over the time course of the infection, and many of these 114 genes encode proteins involved in immune response, apoptosis, cell adhesion, stress response, and transcription. This study also revealed a broad correlation between gene expression profiles and the progression of BSE in cattle. At 21 months postinoculation, the largest number of differentially regulated genes was detected, suggesting that there are many pathogenic processes in the animal brain even prior to the detection of infectivity in the central nervous systems of these orally infected cattle. Moreover, evidence is presented to suggest that it is possible to predict the infectious status of animals using the expression profiles from this study. © 2009, American Society for Microbiology. All Rights Reserved.
Created from Fastlane, Scopus look-up